Christian views from the monthly magazine Thought and Time - YANG, Shihai (Journal of Research for Christianity in China (JRCC), 2025)
Thought and Time is a journal founded during the movement to the southwest China during the Anti-Japanese War, and the magazine remains as interested in Christianity. This paper analyzes their views on Christianity by introducing the articles on Christianity in the magazine, and finds that intellectuals during the Anti-Japanese War had a deeper understanding of Christianity and a more three-dimensional understanding of Western culture than before, which is also a typical stage in the history of Sino-Western cultural exchange. Of course, there are also unavoidable limitations of The Times and thinking.
Keywords: Thought and Time; Christian views; Chinese traditional culture